2008
DOI: 10.1111/j.1600-0609.2008.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication and biological roles of RhoH in acute myeloid leukaemia

Abstract: The Rho family of small GTPases, including Rho, Rac and Cdc42, has been well characterised as a molecular switch that transduces signals from plasma membrane to the downstream effectors. RhoH gene, a member of the Rho family, is specifically expressed in haematopoietic cells. The known function of RhoH is antagonising Rac and mediating activation of ZAP-70 in T lymphocytes; however, biological roles of RhoH in myeloid cells remain unknown. Here, we analysed the prognostic implication of the expression level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…In contrast, RHOH, encoding a hematopoietic-specific, GTPase-deficient member of the Rho GTPase protein family, was first identified as a partner of BCL6 in a fusion transcript resulting from t(3;4)(q27; p13) in a non-Hodgkin lymphoma cell line (33) and was aberrantly overexpressed in B-cell chronic lymphocytic leukemia (CLL), in which it played an essential oncogenic role (34). However, in AML, low expression of RHOH has been shown to be an independent unfavorable prognostic factor for both overall and disease-free survival of the patients and contributes to chemotherapy resistance in leukemia cells (35), implying a tumor suppressor role in AML. Similarly, TAL1 is a common target of chromosomal rearrangements in T-cell acute lymphoblastic leukemia (T-ALL) and is aberrantly expressed in up to 60% of pediatric T-ALL, in which it plays an oncogenic role (36); however, the down-regulation of TAL1 has been frequently observed in AML (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RHOH, encoding a hematopoietic-specific, GTPase-deficient member of the Rho GTPase protein family, was first identified as a partner of BCL6 in a fusion transcript resulting from t(3;4)(q27; p13) in a non-Hodgkin lymphoma cell line (33) and was aberrantly overexpressed in B-cell chronic lymphocytic leukemia (CLL), in which it played an essential oncogenic role (34). However, in AML, low expression of RHOH has been shown to be an independent unfavorable prognostic factor for both overall and disease-free survival of the patients and contributes to chemotherapy resistance in leukemia cells (35), implying a tumor suppressor role in AML. Similarly, TAL1 is a common target of chromosomal rearrangements in T-cell acute lymphoblastic leukemia (T-ALL) and is aberrantly expressed in up to 60% of pediatric T-ALL, in which it plays an oncogenic role (36); however, the down-regulation of TAL1 has been frequently observed in AML (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Low RhoH levels are connected with an upregulation of IL3-dependent cell growth, STAT5 activity and an increase of CD123 surface expression that has been described in AML patients (GƱndogdu et al, 2010). Multivariate analysis demonstrated that low expression of RhoH was an independent unfavorable prognostic factor for both overall and disease-free survival of AML in the intermediate risk group (Iwasaki et al, 2008). Activation of Notch signal pathway (expression of Notch1, Jagged1 and Delta1 as members of this pathway) is associated with a poorer prognosis for AML patients with intermediate risk .…”
Section: Other Molecular Marker Genes Expressionmentioning
confidence: 97%
“…The Rho family of small GTPases, including Rho, Rac and Cdc42, functions as critical mediators of signaling pathways from plasma membrane regulating actin assembly, migration, proliferation and survival in hematopoietic cells. RhoH gene, also known as Translocation Three Four (TTF), encodes a 191-amino acid protein belonging to the Rho family (Gu et al, 2005;Iwasaki et al, 2008). Rho H functions as a negative regulator for interleukin 3 (IL3) -induced signals through modulation of the JAK-STAT (Janus KinaseSignal Transducer and Activator of Transcription)-signaling pathway (GƱndogdu et al, 2010).…”
Section: Other Molecular Marker Genes Expressionmentioning
confidence: 99%
“…As mentioned, elevated CD123 expression in AML patients contributes to increased proliferation of leukemic blasts, hyper-activation of STAT-5 and poor prognosis 28 . Low expression levels of RhoH were also described as another factor in poor patient prognosis 45 . These data demonstrate that these two findings might be connected.…”
Section: Cytokines In Aml Proliferation and Prognosismentioning
confidence: 99%